A conceptual framework to study effective short-video platform advertising on Chinese generation Y consumer online purchase intention - Sheng, Mengyan; Kamal Basha, Norazlyn (World Scientific and Engineering Academy and Society, 2022)
The millennial generation is highly linked to modern media, has unfettered access to the Internet to gather vital information and enjoys online shopping. Generation Y consumes information to fulfil the fundamental needs of commodities. An effective short-video advertising strategy should optimize the capabilities of online platforms to guarantee that consumers will see the adverts as relevant, significant, and valuable when they view them. The purpose of this study was to establish a model to assist marketers, advertisers, and short-video platform operators in creating more effective short-video commercials to influence the online buy intentions of varied Chinese consumers. It is suggested that understanding the link between bandwagon indicators, such as popularity rankings, in-app purchase sales volume, and advertising is essential for making the best marketing decisions. In addition, bandwagon perception is important for boosting the perceived advertising value and buying intent through mediating advertising value.